Effect of Dyslipidaemia and Metabolic Function in Coronary Heart Disease with Type 2 Diabetes Mellitus - In Tertiary Care Center - Akansha Singh; Ranjit S. Ambad; Roshan Kumar Jha (Journal of Pharmacy and Bioallied Sciences)
Introduction: T2DM is strongly associated with an increased prevalence of cardiovascular disease (CVD). It has been established that CVD is the main cause of mortality among patients with type 2 diabetes mellitus (T2DM) contributing to 80% of fatal outcomes. The consistent relationship between T2DM and CVD is well-established in observational studies, meta-analyses, and has an easily discernible biological mechanism. Aim and Objectives: This was a cross-sectional study consisting of 100 subjects of diabetic and non-diabetic with CHD attending medicine outpatient department (OPD). Result and Conclusion: The study highlights that diabetes significantly exacerbates the metabolic and cardiovascular risks in coronary heart disease (CHD) patients, affecting lipid profiles, glycemic control, and long-term survival. Effective management of these parameters is crucial to improving outcomes in diabetic CHD patients. Postoperative morbidity and early mortality were not substantially affected by diabetes; however, long-term survival in diabetic CHD patients was markedly diminished, highlighting the enduring effects of diabetes on cardiovascular health.